1991
DOI: 10.1523/jneurosci.11-12-03877.1991
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative and degenerative changes in striatal spiny neurons in Huntington's disease: a combined study using the section-Golgi method and calbindin D28k immunocytochemistry

Abstract: Dysmorphic alterations of dendritic arbors and spines in spiny striatal neurons were identified in section-Golgi impregnations of moderate and severe grades of Huntington's disease (HD). These alterations could be characterized as either proliferative or degenerative changes. Proliferative changes included prominent recurving of distal dendritic segments, short-segment branching along dendrites, and increased numbers and size of dendritic spines. Degenerative alterations consisted of truncated dendritic arbori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
173
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(197 citation statements)
references
References 64 publications
24
173
0
Order By: Relevance
“…Segment length is represented on the abscissa and spine density on the ordinate. McNeil1 et al, 1990), in hippocampal neurons of aged humans (Buell and Coleman, 1981;Flood et al, 1985Flood et al, , 1987, and in striatal cells in moderate grade Huntington's disease (Graveland et al, 1985;Ferrante et al, 1991). In each of these instances, however, the effects are transient and dendritic proliferation is followed by degeneration.…”
Section: Dutu Analysis: Critique and Interpretationsmentioning
confidence: 99%
“…Segment length is represented on the abscissa and spine density on the ordinate. McNeil1 et al, 1990), in hippocampal neurons of aged humans (Buell and Coleman, 1981;Flood et al, 1985Flood et al, , 1987, and in striatal cells in moderate grade Huntington's disease (Graveland et al, 1985;Ferrante et al, 1991). In each of these instances, however, the effects are transient and dendritic proliferation is followed by degeneration.…”
Section: Dutu Analysis: Critique and Interpretationsmentioning
confidence: 99%
“…16 The presence of the abnormal huntingtin protein in cells sets off a complex and poorly understood series of deleterious and progressive biochemical events leading in neurons to stress, physiological dysfunction, compensatory responses, neurodegeneration, and eventually cell death. Neurodegeneration appears to be quite a prolonged process, as evidenced by signs of chronic neuroplasticity 17,18 and of the slow involution of neurons with gradual loss of synapses, dendritic spines, dendritic branches, axonal segments, and supportive cytoplasmic resources such as mitochondria and organelles involved in the biosynthesis, modification, transport, and degradation of cellular molecules. The process of neurodegeneration ends in cell death, and dead and dying neurons in situ can cause local inflammatory responses and possibly worsen conditions in their immediate vicinity.…”
Section: Neurodegenerationmentioning
confidence: 99%
“…Decreased numbers of neurons immunoreactive for calbindin D28k, a Ca2+-binding protein present in a subset of striatal medium-sized spiny neurons has also been reported. Interestingly, Golgi staining studies showed that before death many striatal GABAergic neurons show morphological abnormalities in moderate grades of HD [64]. Changes in immunoreactivity for calbindin or Golgi staining indicate the presence of proliferative dendritic changes early in the disease.…”
Section: Neuropathological Findingsmentioning
confidence: 99%